2019
DOI: 10.3390/pr7120902
|View full text |Cite
|
Sign up to set email alerts
|

A DEA Approach for Assessing the Energy, Environmental and Economic Performance of Top 20 Industrial Countries

Abstract: Due to growing concerns of global warming, reducing carbon emissions has become one of the major tasks for developing countries to meet the national demand for energy policies. The objective of this study is to measure the energy consumption, carbon emission and economic-environmental efficiency in terms of the environmental performance of the top 20 industrial countries by employing a data envelopment analysis (DEA) model from 2013 to 2017. This study used the trilemma of energy efficiency, CO2 emission effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…The documentary has been examined from two angles: (1) the transmission instability during the COVID-19 crisis and (2) the relationship between the COVID-19 indicators and stock market performance and economic uncertainty. We examined recent publications on the economic and financial effects of the COVID-19 pandemic (Iqbal et al 2019a ). Several new publications looked at COVID-19’s financial and socioeconomic consequences (Tlemsani et al 2020 ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The documentary has been examined from two angles: (1) the transmission instability during the COVID-19 crisis and (2) the relationship between the COVID-19 indicators and stock market performance and economic uncertainty. We examined recent publications on the economic and financial effects of the COVID-19 pandemic (Iqbal et al 2019a ). Several new publications looked at COVID-19’s financial and socioeconomic consequences (Tlemsani et al 2020 ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…First is the effect of COVID-19 on the energy sector in determining energy consumption pattern from the raw material of production (oil demand, supply and consumption) to end-product (electricity and end mean of fuel used in the travel and transport industry). Second, how the energy market will reshape a shift and recover after a pandemic or, in other words, how energy market will revive after a pandemic is the most important question of recent times that need answer (Igwe 2020). Endorsing the previous literature, a recent study is extending the theoretical contribution by testing these missing links between the COVID-19 outbreak, energy consumption and CO 2 emission.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Through the case study process, based on stakeholder awareness, Ikram et al [52] identified organizations' management, occupational safety and health management, wages, labor rights, education and training, labor relations, children and slavery, organizational commitment, worker welfare, research and development, altruism, stakeholders, product liability, and social issues in the Pakistani Industry and their role in the SSSCM. It is also believed that true statements of sustainable development practices for stakeholders and consumers tend to take a gradual approach and expand consideration of the business sector [53,54].…”
Section: Supplier Social Sustainabilitymentioning
confidence: 99%